New Advances in Powder Technology - Rajendrachari, Shashanka; Shatokha, Volodymyr; Avar, Baris (IntechOpen, 2023)
This book discusses the basics of powder metallurgy and its interesting applications along with various powder manufacturing techniques. It also reviews the wettability of powders and the properties and applications of various metal powders. It is a great tool for understanding the various parameters of sintering techniques. The book includes seven chapters that describe basic concepts of powder metallurgy, sintering, and related applications.